24-Hour movement behaviours research during the COVID-19 pandemic: a systematic scoping review - Danqing Zhang; Sitong Chen; José Francisco López-Gil; Jintao Hong; Fei Wang; Yang Liu (BMC, 2023)
Abstract Objectives Many studies examining 24-hour movement behaviours based on the 24-Hour Movement Guidelines (24HMG) have been published during the COVID-19 pandemic. However, no comprehensive reviews summarized and synthesized the evidence concerning studies using 24HMG. The aim of this scoping review was to synthesize the evidence from the 24HMG studies published during the pandemic. Methods Three electronic databases (Web of Science, PubMed, EBSCO) were utilized to conduct a literature search. The search procedure adhered to the guidelines set by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Initially, a total of 1339 research articles published in peer-reviewed journals were screened. After eliminating 461 duplicates, 878 articles remained. The titles and/or abstracts of these articles were then cross-checked, and 25 articles were included. Subsequently, two authors independently assessed full-text of articles based on the pre-defined inclusion and exclusion criteria, resulting in the final selection of 16 articles that met the inclusion criteria. Study characteristics (e.g., study population, study design, measurement) were extracted and then summarized. According to the Viable Integrative Research in Time-use Research (VIRTUE) epidemiology, the included studies were further classified into different but interrelated study domains (e.g., composition, determinants, health outcomes). Results The majority of included articles focused on children and adolescents as study population. This study primarily demonstrated that a low prevalence of meeting the 24HMG among children and adolescents during the COVID-19 pandemic. There has been a decline in the percentage of individuals meeting the 24HMG compared to the pre-COVID-19 period. The majority of included studies focused on sociodemographic factors when examining the correlates of meeting the 24HMG, while a few studies assessed factors of other domains, such as social, cultural, and environmental aspects. Conclusion The COVID-19 pandemic had an impact on healthy 24-hour movement behaviours in children and adolescents. In conjunction with the studies conducted during the COVID-19 pandemic, more studies were encouraged to explore the correlates of meeting the 24HMG and the associated health benefits in wider ranges of populations.